2012
DOI: 10.1016/j.apmr.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Cognitive Function to Straight- and Curved-Path Walking in Older Adults

Abstract: Objective To determine whether the cognitive function contribution to straight- and curved-path walking differs for older adults. Design Cross-sectional observational study. Setting Ambulatory clinical research training center. Participants One hundred six people aged 65 years to 92 years, able to walk household distances independently with or without an assistive device, and who scored ≥ 24 on the Mini-Mental State Examination. Intervention Not applicable. Main Outcome Measurements Cognitive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 34 publications
7
74
0
Order By: Relevance
“…We observed that the Trails B test performance was associated with performance on both walking performance tests. Consistent with our findings, prior studies have linked certain aspects of cognition with performance on F8WT and HGS tests (27). The Trails-making test part B measures cognitive skills such as attention, working memory, and cognitive flexibility (all executive functions), as well as psychomotor speed and visuoperceptual abilities (15,28).…”
Section: Discussionsupporting
confidence: 78%
“…We observed that the Trails B test performance was associated with performance on both walking performance tests. Consistent with our findings, prior studies have linked certain aspects of cognition with performance on F8WT and HGS tests (27). The Trails-making test part B measures cognitive skills such as attention, working memory, and cognitive flexibility (all executive functions), as well as psychomotor speed and visuoperceptual abilities (15,28).…”
Section: Discussionsupporting
confidence: 78%
“…During anticipated turns, the patient walks toward the point where he needs to turn while visual information is integrated with other sensory-motor inputs necessary to perform the task [4,14]. This information processing is associated with executive function thought to take place in Brodmann 10.…”
Section: Differences Between Anticipated and Unanticipated Turnsmentioning
confidence: 98%
“…We used fNIRS during actual walking to examine frontal lobe activation before and during FOG. We focused on turns since they are one of the most common provokers of FOG and since turns are associated with increased executive function demands [14] and place greater demands on the coupling between posture, gait and perceptual processing and planning [17,27]. Accordingly, we hypothesized that frontal activation patterns would be altered during turns with FOG, compared to turns without FOG.…”
Section: Introductionmentioning
confidence: 99%
“…25 Cognitive function was evaluated with the Digit Symbol Substitution Test (DSST), where the subject copies as many novel symbols corresponding to numbers as possible in 90 s, providing a reliable measure of psychomotor speed, attention, and visual scanning. [26][27][28] A general survey was also used, addressing smoking status, frequency of COPD exacerbations, and health-care use (number of ED or hospital visits in the prior year).…”
Section: Other Measuresmentioning
confidence: 99%